Color attributes and myoglobin chemistry exhibit relationships with tenderness and calpain-1 abundance in postmortem Longissimus lumborum muscles from Holstein heifers. (July 2022) - Cooper, Jade V.; Suman, Surendranath P.; Burdick, Katelyn S.; Sutovsky, Peter; Lonergan, Steven M.; Lorenzen, Carol L.
Abstract: The objective of this study was to determine the extent that myoglobin and beef color are associated with calpain-1 relative abundance relative and tenderness. Longissimus lumborum (LL) samples from the left side of Holstein beef carcasses ( n = 31) were collected immediately post-evisceration for 0 h analyses. At 48 h postmortem six steaks were removed from the right side of each carcass for analyses at 48 and 336 h postmortem. Myoglobin concentrations resulted in negative correlations ( P < 0.05) to Warner-Bratzler shear force (WBSF) values at 336 h postmortem. L*, a*, and b* values at 48 h resulted in positive correlations ( P < 0.05) with WBSF values at 48 and 336 h. Values for b* at 336 h had positive correlations with calpain-1 concentration at 0 and 336 h. Data from this study indicate a potential relationship between myoglobin concentration and meat color with tenderness aspects and calpain-1 relative abundance.